AUTISTIC SPECTRUM DISORDER (TEA) : CONCEPT, INTERVENTIONS AND LEARNING - Adriana Santin Ferreira, Vanderléia; Joaquina de Borba, Nara; Palhares dos Santos, Tainara; Romani Franciscao, Cristiane (Revista Gênero e Interdisciplinaridade, 2024)
The objective of the text was to understand the concept of autistic spectrum disorder (ASD) and possible mediations in socialization, learning and quality of life of individuals with ASD. The deepening of knowledge opens a series of possibilities for methodologies of interaction, support, cognitive and social development of the person in question, as well as their families and/or responsible. The speed in the diagnosis is of great value to the development of the potentialities of the individual and his social inclusion. Educational practice in ASD holders still needs to go a long way to actually ensure their inclusion and develop their autonomy.